The Effect of Academic Stress and Mental Anxiety among the Students of Khulna University - Md. Fajlay Rabbi; Md. Sefatul Islam (Papanda Publisher, 2024)
The mental health issues that students encounter is becoming more widely recognized in today's educational setting. It explores the effect of academic stress and mental anxiety among the students of Khulna University. This study investigates the complex relationship between academic pressures, mental distress, and the general well-being of Khulna University students by using a mixed-methods research technique. The study utilizes a combination of qualitative interviews and quantitative surveys to obtain a thorough understanding of students' experiences. The relationship between academic stress variables, anxiety levels, and academic performance can be analyzed quantitatively to find patterns and connections. Simultaneously, qualitative interviews offer a refined comprehension of the students' subjective experiences, and feelings of stress and anxiety. The results provided insight into the frequency of academic stressors, and how these affect students' mental health. This result shows that 15.68% student suffer from high level of academic stress. And 76.8% student suffer from academic stress in some point of their academic life. This result shows that 16.7% reporting extremely severe anxiety. And 61.1% student suffer from anxiety in some point. This study has implications that go beyond Khulna University; it provides information that legislators, educators, and mental health professionals can use. This study is to contribute to the creation of focused treatments and support systems to promote a healthy academic environment for students by studying the dynamics of academic stress and mental anxiety. The study highlights the need for a holistic approach to education that prioritizes mental health and fosters an environment conducive to academic success and personal growth. It aims to add meaningful knowledge to the discourse on student well-being.